Author Correction: High-performance compliant thermoelectric generators with magnetically self-assembled soft heat conductors for self-powered wearable electronics - Byeongmoon Lee (Nature Portfolio, 2021)
A Correction to this paper has been published: https://doi.org/10.1038/s41467-021-21629-y